THE EFFECT OF A YOGIC STRESS MANAGEMENT TECHNIQUE IN A CALL CENTRE - Maharaj, Shobha (My University, 2011)
The pace of change and intense competition in business has resulted in individual well-being and organisational effectiveness being affected. A possible solution to alleviating stress amongst employees is a yogic stress-management technique, Sudarshan Kriya, which has been shown to alleviate stress at many levels. The study evaluated the effects of Sudarshan Kriya on individual well-being and certain organisational objectives, within a call centre. This study is a pure experimental design using pre-tests and post-tests administered to randomly selected participants. The study showed Sudarshan Kriya was successful in reducing burnout, the number of physical symptoms of stress and rustout amongst participants. No evidence of the predicted changes in organisational objectives was found. Although Sudarshan Kriya was successful in improving individual well-being, the predicted impact on organisational objectives were not obvious. Together with other programmes, it can be used to achieve transformation within organisations. Heightened employee well-being is reflective of organisation well-being
MBA thesis - WBS
Keywords: Call Centres; Stress management